2016
DOI: 10.3748/wjg.v22.i8.2592
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pyloriinfection is not associated with nonalcoholic fatty liver disease

Abstract: H. pylori infection is not a risk factor for NAFLD as indicated by HSI or NAFLD-LFS. Prospective, large-scale studies involving liver biopsies should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
78
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 46 publications
3
78
2
3
Order By: Relevance
“…Of these potential eligible articles, we excluded 13 articles (characteristics of excluded articles see Table ) by examining the abstracts or full‐texts carefully for more detailed assessment. Finally, fifteen studies met the inclusion criteria and were included in our meta‐analysis. The detailed flowchart of selection process of eligible studies is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these potential eligible articles, we excluded 13 articles (characteristics of excluded articles see Table ) by examining the abstracts or full‐texts carefully for more detailed assessment. Finally, fifteen studies met the inclusion criteria and were included in our meta‐analysis. The detailed flowchart of selection process of eligible studies is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…These studies were published between 2013 and 2018, three of which were conference abstracts . Our meta‐analysis contained eleven cross‐sectional studies, two case‐control studies, one retrospective cohort study, and one prospective multicenter cohort . Eleven of these studies were from Asia, two studies from the United States, one from Greece, and one from Egypt .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, we describe for the first time the association between high fat dietinduced NAFLD and enhanced Helicobacter genus detection. Even though is a controversial issue [45,46], it has been suggested the role of Helicobacter pilory as a contributing factor in the progression of NAFLD [47][48][49], considering its eradication as effective preventive or treatment measures [50,51]. Interestingly, Helicobacter genus was dramatically reduced by quercetin treatment in our model of NAFLD, corroborating its anti-Helicobacter activity observed in in vitro and in vivo models of infection [52,53], and supporting therapeutic potential of quercetin for prevention of the spectrum of non-alcoholic fatty liver diseases.…”
Section: Thus Quercetin Reduced the Increased Firmicutes/bacteroidetesmentioning
confidence: 99%